A literature review on coliform detection methods in wáter sources: Recent international developments - Jara-Vilca, Rocio (2023)
The consumption of contaminated water, especially total coliforms, causes multiple intestinal diseases and is currently a latent problem. In this sense, the objective of the research was to analyze the detection methods for microbiological analysis of water at international level. The literature review was conducted based on data from the National Center for Biotechnology Information (NCBI), Latin American and Caribbean Literature on Health Sciences (LILACS) and Scopus, from 2012 to December 2022. Data analysis was performed according to the selected articles and their origin. Co-authorship networks were performed with VOSviewer software. The results show that studies based on water quality analysis methods began to stand out during the years 2021 and the country where research was developed with greater emphasis was the United States. It is concluded that molecular methods are a good alternative for water quality analysis because they are fast and specific.